The Effect of the Word Detective Technique to Improve Vocabulary Skills of the Second-Year Students of Madrasah Tsanawiyah Putri At-Tahzib (Islamic Junior High School) - Islami, Nur Laily; Zamzam, Ahmad; Putera, Lalu Jaswadi (Journal of Authentic Research, 2026)
This study aims to investigate the effect of the Word Detective technique on improving the vocabulary skills of eighth-grade students at MTs. Putri At-Tahzib. The background of the study is based on initial observations showing that most students have low vocabulary skills and are less actively involved in English learning. This study used a quasi-experimental design with two groups: a control group taught conventionally and an experimental group taught using the Word Detective technique. The research sample consisted of 55 students selected through a total sampling technique. Data collection was carried out through a pre-test and post-test with an instrument in the form of 20 multiple-choice questions that have been validated and have a high level of reliability (Cronbach's Alpha = 0.798). The results of the analysis showed that the experimental group experienced an increase in average scores from 52.86 in the pre-test to 74.46 in the post-test, while the control group increased from 51.30 to 63.33. The independent samples t-test yielded a calculated t-value (5.297) greater than the t-table (2.006) at a significance level of 0.05, meaning the alternative hypothesis (Hₐ) was accepted and the null hypothesis (H₀) was rejected. This finding proves that the Word Detective technique has a significant influence in improving students' vocabulary skills. The implications of this study indicate that the Word Detective technique can be an effective learning strategy to improve students' vocabulary skills through an active approach that utilizes contextual clues and word structures. This technique is recommended for application in English learning because it encourages active and meaningful student involvement in the vocabulary acquisition process.